The development of “PICPACK” (Pictorial Book in Packaging) module to enhance adolescents knowledge of visual communication / Siti Soraya Ramli - Ramli, Siti Soraya (2017)
The intention of this research is to examine the usefulness of pictorial book for teaching and learning packaging topic in Visual Art Education (VAE). This research also assesses its effectiveness in the classroom and intrinsic motivation of the students. The pictorial book was developed using ADDIE model supported by Zone of Proximal Development (ZPD) – Scaffolding by Lev Vygotsky (1978) and built using the Design Develop Research (DDR) as a research design by considering the design, pedagogical and the contents of its learning material. The PicPack Module was evaluated by two experts during the pre-production and post-production level. One is an expert of VAE content and another one is an expert in pictorial books. After getting consensus from the experts, the research was conducted through Single-Group Post-Test-Only Design upon purposive sampling consisting of one VA teacher and 50 form four VA students with 23 males and 27 females. Students showed positive attitudes toward learning using the PicPack Module. Based on the findings, the development of the PicPack Module is relevant and has its possibilities to be implemented in secondary level of art education in Malaysia.